Optimizing the Pictorial Compacted Data Detection Process for Working at the Noisy Environment, Using Reversible Symmetrical Codes - Shafafi, K.; Samanfar, A.; Saremian, E.; Moradtalab, O. (2009 International Conference on Information and Multimedia Technology, 2009)
Variable-length codes, using source statistical features, improve the encoding. However, using these codes can results in error propagation in bit string transmitted to noisy transmission environments. This paper has used reversible symmetrical codes in the bit string obtained from JPEG compressor in order to overcome this problem. several examples of reversible code design algorithm have been reviewed and a symmetrical code based on Huffman code has been analyzed and deigned for JPEG compressor. JPEG compressor has been simulated by Huffman standard code and by reversible symmetrical code and the amount of their compression has been compared for several pictures Also, optimization of detection trend in noisy condition has been displayed.